Menjaga Identitas di Negeri Syariat: Menelisik Komunikasi Non Verbal Anggota Komunitas Lesbian di Kota Langsa - Agesti, Mita; Samsuar, Samsuar; Rusli, Rusli; Zulkarnain, Zulkarnain (DEPARTEMENT OF COMMUNICATION AND ISLAMIC BROADCASTING STUDIES, 2024)
This research examines the interactions of members and the lesbian community in Langsa City, an area in Aceh that implements Islamic law in Indonesia. This research uses Ervin Goffman's dramaturgical theory. The research uses a qualitative approach with phenomenological methods. Collecting data by conducting in-depth and regular interviews with four lesbian people. Their appearance in public is a very taboo phenomenon in this area, and this condition is a challenge for lesbians to establish communication with society so that their existence can be accepted. Important findings in this research show how members of the lesbian community develop communication and interactions very carefully, using more symbolic language when they are in public places. The symbols or signals used by the lesbian community to communicate are very specific when in public places, namely, starting from the way they dress, the language used, and physical touch such as touching hands, glances, and eye contact